Five Programs to Improve Student’s Understanding of Religious Teaching at Islamic Educational Institutions - Desma Yenti, Lili; Indria, Anita; Hendrisab, Hendrisab (Ahlussunnah: Journal of Islamic Education, 2023)
This research aims to determine the implementation of the program used in developing morals for students of Madrasah Diniyah Takmiliyah al-Jami'ah Indonesian Da'wah Academy Aqabah Bukittinggi, evaluating the program used in developing morals for students of Madrasah Diniyah Takmiliyah Al-Jami'ah Indonesian Da'wah Academy Aqabah Bukittinggi and for inhibiting and supporting factors in implementing the moral development program for students at Madrasah Diniyah Takmiliyah al-Jami'ah Indonesian Da'wah Academy Aqabah Bukittinggi. This research uses a qualitative descriptive approach with data collection techniques: observation, interviews and documentation. After all the data was collected, the author carried out classification, editing, and adjustments to the character and type of each data, then filtered it into a final conclusion. Based on the results of research conducted by the author, show that the Moral Development Program for students at Madrasah Diniyah Takmiliyah al-Jami'ah Indonesian Da'wah Academy Aqabah Bukittinggi can be seen from various aspects, namely: implementation of the student moral development program, namely the main program and supporting programs. The main program is a weekly study program carried out in the dormitory. Then the supporting programs are the muhadhatsah, muhadharoh, tahsin, tahfizh and lailatul Quran programs. All programs aim to ensure that students have good manners or good morals.